The Relationship Between Parenting Style and Independent Character Toward IPAS Learning Outcomes among Fifth-Grade Elementary School - Ni Luh Dina Adriani; Desak Putu Parmiti; Basilius Redan Werang (Indonesian Values and Character Education Journal, 2025)
Low IPAS learning outcomes, along with variations in parenting styles and students’ levels of independent character, indicate a problem that requires empirical investigation. This study aims to examine the relationship between parenting style and independent character on IPAS learning outcomes among fifth-grade students in the 2023/2024 academic year. The research employed an ex post facto design. The population consisted of 181 fifth-grade students, with a sample of 123 students selected through random sampling techniques. Data were collected using questionnaires to measure parenting style and students’ independent character, as well as documentation of IPAS Final Semester Examination (UAS) scores. The analysis results revealed that parenting style contributed 4.3%, independent character contributed 66.6%, and the combination of both variables contributed 68.5% to students’ IPAS learning outcomes. These findings indicate that independent character plays a more dominant role than parenting style in directly influencing IPAS learning outcomes, although both variables are interconnected. The study implies that systematic strengthening of students’ independent character within school practices, supported by positive parenting at home, is essential for improving academic achievement. Strengthening collaboration between schools and parents through structured programs focused on fostering self-regulated learning, responsibility, and autonomy may serve as an effective strategy to enhance student performance. Based on these findings, future research is recommended to employ longitudinal designs to obtain a more comprehensive understanding of the dynamic relationships among variables and to explore potential mediating or moderating factors.